2015
DOI: 10.18632/oncotarget.3556
|View full text |Cite
|
Sign up to set email alerts
|

Anterior gradient protein 2 expression in high grade head and neck squamous cell carcinoma correlated with cancer stem cell and epithelial mesenchymal transition

Abstract: Anterior gradient protein 2 (AGR2) is a novel biomarker with potential oncogenic role. We sought to investigate the diagnostic and prognostic role of AGR2 on head and neck squamous cell carcinoma (HNSCC) with an emphasis on its correlation of cancer stemloid cells (CSC) and epithelial mesenchymal transition (EMT). We found that AGR2 protein levels were higher in HNSCC than in normal oral mucosa. High levels of AGR2 were associated with the T category, pathological grade and lymph node metastasis of HNSCC. Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 52 publications
3
58
0
Order By: Relevance
“…CD44, KLF4, ALDH1 and SOX2). Our previous data have proven that C4.4A and AGR2 were activated in SCCHN and associated with EMT or cancer stem cell . In this study, both C4.4A and AGR2 have a strong correlation and a similar expression pattern with TRAF6.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…CD44, KLF4, ALDH1 and SOX2). Our previous data have proven that C4.4A and AGR2 were activated in SCCHN and associated with EMT or cancer stem cell . In this study, both C4.4A and AGR2 have a strong correlation and a similar expression pattern with TRAF6.…”
Section: Discussionsupporting
confidence: 64%
“…5B). In addition, our previous data have proved that C4.4A and AGR2 were activated in SCCHN and associated with EMT or CSCs [39,44]; moreover, both of them have a strong correlation and a similar expression pattern with TRAF6 (C4.4A, P < 0.01, r = 0.3694; AGR2, P < 0.001, r = 0.4107; Fig. 5B and C).…”
Section: Traf6 Was Correlated With Emt and Cscs In Mice And Human Scchnmentioning
confidence: 61%
“…31 Here, we revealed that AGR2 is also overexpressed at the protein level in pancreatic CSC compared with non-stem cancer cells. Taken together, our data indicate that AGR2 plays an important role in PDAC initiation and development, potentially by regulating the maintenance of stemness and progenitor cell differentiation.…”
Section: Discussionmentioning
confidence: 76%
“…c), suggesting that FOXA1 may not affect the generation of CSCs. The colony formation assay is widely used to evaluate the proliferative ability of immature cells . As shown in Figure (d,e), the number of colonies derived from shFOXA1 MCF‐7 cells significantly decreased compared to control cells.…”
Section: Resultsmentioning
confidence: 96%
“…The colony formation assay is widely used to evaluate the proliferative ability of immature cells. (28,46) As shown in Figure 5(d,e), the number of colonies derived from shFOXA1 MCF-7 cells significantly decreased compared to control cells. Taken together, these findings indicate that FOXA1 appears to work as a factor in the proliferation rather than maintenance of stemness-related genes or the activation of CSCs.…”
Section: Ectopic Foxa1 Expression In Mammospheres Is Correlated To 4-mentioning
confidence: 85%